2017
DOI: 10.1364/ol.42.000219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the photon orbital angular momentum on electric dipole transitions: negative experimental evidence

Abstract: We describe an experiment of atomic spectroscopy devoted to ascertaining whether the orbital angular momentum (OAM) of photons has the same property of interacting with atoms or molecules as occurs for the spin angular momentum (SAM). In our experiment, rubidium vapors are excited by means of laser radiation with different combinations of OAM and SAM, particularly selected to inhibit or enhance the fluorescence according to the selection rules for the electric dipole transitions between the fundamental state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…For the simplest process, single-photon absorption, this conclusion has indeed borne out by recent experimental evidence [111]. For higher order processes involving more than single-photon events, studied under conditions that invalidate the paraxial approximation-including a near-field configuration or in the vicinity of a beam focus-the presence of longitudinal fields [65] and any additional Gouy phase [112] admit an additional dependence on l, not exhibited in the present simplified analysis.…”
Section: Transitions and Motionssupporting
confidence: 66%
“…For the simplest process, single-photon absorption, this conclusion has indeed borne out by recent experimental evidence [111]. For higher order processes involving more than single-photon events, studied under conditions that invalidate the paraxial approximation-including a near-field configuration or in the vicinity of a beam focus-the presence of longitudinal fields [65] and any additional Gouy phase [112] admit an additional dependence on l, not exhibited in the present simplified analysis.…”
Section: Transitions and Motionssupporting
confidence: 66%
“…Comparing the results of the iron dichroism experiment with the well known XMCD spectra of iron suggests that there is a similar transfer of orbital angular momentum between the beam electron and the internal atomic states, in contrast to the case of optical vortices, in which no orbital angular momentum transfer can arise in dipole transition (Andrews et al, 2004;Babiker et al, 2002;Jáuregui, 2004) (see also (Alexandrescu et al, 2005)) nor any were observed (Araoka et al, 2005;Giammanco et al, 2017;Lö✏er et al, 2011). The mechanisms of the atomic-vortex interactions are quite di↵erent in the optics and electron cases -in the optics case the interaction Hamiltonian arising from the minimal coupling prescrip-tion does not exhibit the required chirality to mediate orbital angular momentum transfer, in contrast to the long-range Coulomb interaction between the atomic and vortex electrons (Lloyd et al, 2012a,c).…”
Section: Interaction With Mattermentioning
confidence: 83%
“…The first attempt at tackling this question utilized QED methods and determined that, for dipole transitions, the OAM of light is transferred to the mechanical motion of particles only; the lowest-order interaction required for OAM to be transferred to an electron is through E2 transitions [218]. While certain other non-QED analyses argued for OAM transferral in the dipole approximation, this failed to be observed in experiments [219,220]. Very recently, the QED theory was experimentally vindicated in the observation of modified selection rules for absorption of OAM light in which two units of angular momentum, 2 , were transferred to the valence electron of a 40 Ca + ion through an E2 transition-one quantum of angular momentum from the spin angular momentum, and one from the OAM [221].…”
Section: B Original Predictions Of Qedmentioning
confidence: 99%